2009
DOI: 10.1111/j.1365-313x.2009.04046.x
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis MPK6 is involved in cell division plane control during early root development, and localizes to the pre-prophase band, phragmoplast, trans-Golgi network and plasma membrane

Abstract: ). † These two authors contributed equally to this work. SUMMARYThe proper spatial and temporal expression and localization of mitogen-activated protein kinases (MAPKs) is essential for developmental and cellular signalling in all eukaryotes. Here, we analysed expression, subcellular localization and function of MPK6 in roots of Arabidopsis thaliana using wild-type plants and three mpk6 knock-out mutant lines. The MPK6 promoter showed two expression maxima in the most apical part of the root meristem and in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(119 citation statements)
references
References 60 publications
6
111
1
Order By: Relevance
“…As previously reported (Mü ller et al, 2010), we found that about the 26% to 43% of mpk6-2 seedlings showed major developmental defects with a no root or short root phenotype, that were recovered after 10 to 12 d. Noteworthy, dark-grown mpk6-2 mutants displaying the no root-short root phenotypes also had a very short hypocotyl, suggesting an overall effect of the mpk6-2 mutation on seedling development, though with incomplete penetrance (Supplemental Fig. S12).…”
Section: Et Sensitivity Assaysupporting
confidence: 63%
“…As previously reported (Mü ller et al, 2010), we found that about the 26% to 43% of mpk6-2 seedlings showed major developmental defects with a no root or short root phenotype, that were recovered after 10 to 12 d. Noteworthy, dark-grown mpk6-2 mutants displaying the no root-short root phenotypes also had a very short hypocotyl, suggesting an overall effect of the mpk6-2 mutation on seedling development, though with incomplete penetrance (Supplemental Fig. S12).…”
Section: Et Sensitivity Assaysupporting
confidence: 63%
“…The MT pellet contained a prominent fraction of MPK4 ( Figure 5), although there was still a substantial amount of MPK4 left in the supernatant. This suggests that not all of the MPK4 associates with MTs but that some also associates with other cellular compartments, as has been recently described for MPK6 (Mü ller et al, 2010). The addition of recombinant 63His-tagged MAP65-1 did not significantly improve the yield of MPK4 in the MT pellet.…”
Section: Association Of Mpk4 With Mtssupporting
confidence: 59%
“…These distinct root hair phenotypes and the disturbed cell expansion in both mutants suggest aberrant MT organization. The analysis of MT organization was initially conducted by whole-mount tubulin immunofluorescence labeling in roots (Mü ller et al, 2010) of both anp2 anp3 and mpk4 mutants and compared with labeling in their respective wild types. Cortical MTs appeared heavily bundled and showed random configurations in all swollen epidermal cells of both mutants within root meristem regions (cf.…”
Section: Mt Organization In Anp2 Anp3 and Mpk4 Mutantsmentioning
confidence: 99%
“…Arabidopsis thaliana wild-type Columbia-0 (Col-0) and wild-type Wassilewskija plants and the mutants KatE2 (Oelze et al, 2012), erf6 (SAIL_1236_H11), mdh (Hameister et al, 2007), mpk6-2 (Müller et al, 2010), mpk6-3 (Bethke et al, 2009, stn7 (Pesaresi et al, 2009), tpt1 (Schneider et al, 2002), and tpt2 (Schmitz et al, 2012) were grown in soil culture (1:1:1 mixture of Frühsdorfer Erde Klocke P, perlite, and vermiculite) for 4.5 weeks under the following conditions: 10 h of light, 80 mmol quanta m 22 s 21 , 23°C, and 14 h darkness at 18°C; 55% relative humidity. Except for the KatE2 mutant, all mutants used in this study are T-DNA exon insertion mutants (Supplemental Figure 4).…”
Section: Plant Growth and Treatmentsmentioning
confidence: 99%